Literature Study: Antibacterial Activity Test on Deodorant Preparations Containing Natural Ingredients - Nabila Larista Riskiana , Nabila Larista Riskiana; Nabila Putri Rahmawati, Nabila Putri Rahmawati; Sheme Aonido , Sheme Aonido; Firda Senja Maelaningsih , Firda Senja Maelaningsih (Jurnal Medika Farmaka, 2024)
Introduction: Body odor is a common issue caused by bacterial activity, especially Staphylococcus epidermidis. The use of synthetic chemical deodorants often raises concerns regarding long-term health impacts. The purpose of this literature study is to assess the antibacterial effectiveness of natural deodorants as a safer alternative. Methods: This literature study analyzed five articles that tested antibacterial properties in natural deodorants, using the MHA (Muller-Hinton Agar) and Nutrient Agar methods. Results: Shows that ethanol extract of cherry leaves (Muntingia calabura) at a concentration of 40% has the highest antibacterial activity, with an inhibition zone of 34.25 mm, almost equivalent to the positive control. Extracts of beluntas leaves and jelantir leaves also showed good antibacterial activity, although not as effective as cherry leaf extract. Conclusion: This literature study confirms that natural ingredients have the potential to be effective active ingredients in deodorant products and offer a more environmentally friendly alternative compared to synthetic ingredients. Further research is needed to optimize the formulation and understand the mechanism of action of active compounds in plant extracts. Keywords: Antibacterial, Body odor, Deodorant, Staphylococcus epidermidis